MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MELALUI MODEL PROBLEM BASED LEARNING SISWA KELAS III SDN DUREN SAWIT 02 JAKARTA TIMUR - Fitria Tiara Angel; Tunjungsari Sekaringtyas; Yurniwati Yurniwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the critical thinking skills of third-grade students at SDN Duren Sawit 02, East Jakarta, through the implementation of the Problem Based Learning (PBL) model. This study employed a Classroom Action Research approach, conducted in three cycles consisting of the planning, implementation, observation, and reflection stages. The research subjects consisted of 25 third-grade students. Data were collected through observation and critical thinking skill tests, then analyzed using quantitative and qualitative descriptive methods. The results showed that the implementation of the PBL model was able to improve students’ critical thinking skills from 20% in the pre-intervention phase to 28% in Cycle I, 60% in Cycle II, and 84% in Cycle III. Additionally, teacher activity reached 76.47% in Cycle I, 88.23% in Cycle II, and increased to 100% in Cycle III. Meanwhile, student engagement reached 64.71% in Cycle I, 76.47% in Cycle II, and increased to 94.11% in Cycle III. These results indicate that the implementation of the PBL model is effective in improving students’ critical thinking skills in science lessons on the topic of energy conservation.